Host 3' flap endonuclease Mus81 plays a critical role in trimming the terminal redundancy of hepatitis B virus relaxed circular DNA during covalently closed circular DNA formation. - Hu Zhang; Quanxin Long; Yuanjie Liu; Alexander L Marchetti; Cheng-Der Liu; Ning Sun; Haitao Guo (PLoS Pathogens)
Hepatitis B virus (HBV) relaxed circular DNA (rcDNA) possesses an 8-9 nucleotide-long terminal redundancy (TR, or r) on the negative (-) strand DNA derived from the reverse transcription of viral pregenomic RNA (pgRNA). It remains unclear whether the TR forms a 5' or 3' flap structure on HBV rcDNA and which TR copy is removed during covalently closed circular DNA (cccDNA) formation. To address these questions, a mutant HBV cell line HepDES-C1822G was established with a C1822G mutation in the pgRNA coding sequence, altering the sequence of 3' TR of (-) strand DNA while the 5' TR remained wild type (wt). The production of HBV rcDNA and cccDNA in HepDES-C1822G cells was comparable to wt levels. Next-generation sequencing (NGS) analysis revealed that the positive (+) strand DNA of rcDNA and both strands of cccDNA predominantly carried the wt nt1822 residue, indicating that the 5' TR of (-) strand DNA serves as the template during rcDNA replication, forming a duplex with the (+) strand DNA, while the 3' TR forms a flap-like structure, which is subsequently removed during cccDNA formation. In a survey of known cellular flap endonucleases using a loss-of-function study, we found that the 3' flap endonuclease Mus81 plays a critical role in cccDNA formation in wild-type HBV replicating cells, alongside the 5' flap endonuclease FEN1. Additionally, we have mapped the potential Mus81 and FEN1 cleavage sites within the TR of nuclear DP-rcDNA by RACE-NGS analyses. The overlapping function between Mus81 and FEN1 in cccDNA formation indicates that the putative 5' and 3' flap formed by TR are dynamically interchangeable on rcDNA precursor. These findings shed light on HBV rcDNA structure and cccDNA formation mechanisms, contributing to our understanding of HBV replication cycle.